Quality change in Brazilian automobiles - Renato Fonseca (Institute for Applied Economic Research (ipea), 2015)
In this paper I investigate the quality evolution of Brazilian autos. To measure the quality evolution of Brazilian autos, I have assembled a data set for Brazilian passenger cars for the period 1960/94, to which I have applied the hedonic pricing methodology. To the best of my knowledge, this is the first time an index of quality change has been constructed for the Brazilian automobile industry. The results presented here have two major implications. They allow a better understanding of product innovation in Brazil's auto industry, and they provide a clearer explanation of the behavior of auto prices.
Keywords: 330